Diagonal earlobe crease associated with increased epicardial adipose tissue and carotid intima media thickness in subjects free of clinical cardiovascular disease - Murat Ziyrek; Sinan Sahin; Emrah Ozdemir; Zeydin Acar; Serkan Kahraman (KARE Publishing, 2016)
Objective: Atherosclerotic coronary artery disease is a leading cause of death, worldwide. Diagonal earlobe crease (DELC) has been suggested as a simple, noninvasive marker of cardiovascular disease. Although epicardial adipose tissue (EAT) thickness and carotid intima media thickness (CIMT) are closely related to atherosclerosis, the relation between EAT, CIMT, and DELC had yet to be studied. The present objective was to analyze this association. Methods: Subjects were apparently healthy individuals referred to the cardiology outpatient clinic. A total of 65 subjects with DELC and 65 age- and sex-matched controls without DELC were enrolled. EAT thickness and CIMT were measured and analyzed. Results: Epicardial adipose tissue thickness was significantly higher in the DELC group (0.57+-0.12 vs. 0.35+-0.05; p<0.0001). CIMT was also significantly higher in DELC group (0.85+-0.16 vs. 0.60+-0.15; p<0.0001). Correlation analysis showed that CIMT was significantly correlated with EAT thickness (r: 0.594; p<0.0001). Linear regression analysis showed that presence of DELC was independently associated with CIMT and EAT thickness. Conclusion: A significant and independent association between the presence of DELC and increased CIMT and EAT thickness was presently determined, for the first time, in subjects free of clinical cardiovascular disease.